2012
DOI: 10.1542/peds.2011-3291
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Sexual Characteristics in Boys: Data From the Pediatric Research in Office Settings Network

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Recent investigations of pubertal onset in US girls suggest earlier maturation. The situation for US boys is unknown, and existing investigations are outdated and lack information on a key physical marker of male puberty: testicular enlargement.WHAT THIS STUDY ADDS: US boys appear to be developing secondary sexual characteristics and achieving testicular enlargement 6 months to 2 years earlier than commonly used norms, with African American boys entering Tanner stages 2 to 4 earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
196
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(220 citation statements)
references
References 35 publications
17
196
1
6
Order By: Relevance
“…Idiopathic CPP represents 90% of the cases in girls, whereas organic etiologies are more frequent (60% to 70%) in boys. However, these epidemiological data are currently being revised with the new genetic and imaging diagnostic methods (8).…”
Section: Central Precocious Puberty Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic CPP represents 90% of the cases in girls, whereas organic etiologies are more frequent (60% to 70%) in boys. However, these epidemiological data are currently being revised with the new genetic and imaging diagnostic methods (8).…”
Section: Central Precocious Puberty Etiologymentioning
confidence: 99%
“…However, recent epidemiological studies have suggested that the initial pubertal age is decreasing mainly in girls (5-7), but also in boys (8,9). …”
Section: Introductionmentioning
confidence: 99%
“…74 Early signs of puberty manifest around the age of 10 years in girls (breast development) and 11.5 years in boys (testicular enlargement and spermarche-appearance of spermatozoa in first morning void). [75][76][77] Considerable interindividual variation in the timing of pubertal onset exists, ranging from 8 years to 13 years in girls and 9 years to 14 years in boys. 78,79 Subsequent hallmarks of puberty in boys include deepening of the voice and a growth spurt.…”
Section: Puberty and Reproductionmentioning
confidence: 99%
“…During recent decades, age at pubertal onset seems to have markedly declined in girls (2,3,4,5,6) and to a lesser extent in boys (6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%